1986
DOI: 10.1063/1.451548
|View full text |Cite
|
Sign up to set email alerts
|

Unitary quantum time evolution by iterative Lanczos reduction

Abstract: A general unitary time evolution method for wave packets defined on a fixed ℒ2 basis is developed. It is based on the Lanczos reduction of the full N×N Hamiltonian to a p-dimensional subspace defined by the application of H p−1 times to the initial vector. Unitary time evolution in the subspace is determined by exp{−iHpt}, retaining accuracy for a time interval τ, which can be estimated from the Lanczos reduced Hamiltonian Hp. The process is then iterated for additional time intervals. Although accurate result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
559
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 877 publications
(563 citation statements)
references
References 29 publications
2
559
0
2
Order By: Relevance
“…Letting m/M → 0 in the numerical method, it can be shown that the solution given by (21) tends to a small perturbation of the Verlet method formally applied to that equation:…”
Section: Quantum-classical Molecular Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Letting m/M → 0 in the numerical method, it can be shown that the solution given by (21) tends to a small perturbation of the Verlet method formally applied to that equation:…”
Section: Quantum-classical Molecular Dynamicsmentioning
confidence: 99%
“…Integration schemes employing matrix functions apparently have not hitherto been used in practice, except in a few special cases where direct diagonalization is possible. However, since the mid-eighties, starting with a paper by Park and Light [21] on quantum propagators, Lanczos' method has been put to good use in approximating matrix-function vector products. More recently, the excellent convergence properties of this approach have been clarified in [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…38,113,[115][116][117][118] The numerical solution of the time-dependent Schödinger equation has been carried out with an orthogonalised Krylov subspace method. 29,119 …”
Section: Coherent Hole Transfer In Dnamentioning
confidence: 99%
“…1. This approach applies even better to evolving heavy-particle wave packets because the Chebyshev [16,23] or Lanczos [16,24] schemes can be used. These schemes are, first, more efficient than the split method and, second, allow one to take full advantage of the sparse structure of the Hamiltonian in the wavelet basis (see below).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in our example φ n,j |H|φ n,i = 0, if |i − j| ≥ 20. Finally, the time evolution can be computed by standard techniques such as split, Lanczos, or Chebychev methods [16,23,24]. If after the projection on wavelet towers, the Hamiltonian matrix is small enough for a direct diagonalization, Eq.…”
Section: Introductionmentioning
confidence: 99%